Family medicine residents’ barriers to conducting scholarly work - Bammeke, Femi (Can Fam Physician, 2015)
OBJECTIVE: To identify family medicine residents’ barriers to conducting high-quality research for the mandatory family medicine resident scholarly project, as well as to determine possible strategies to encourage research activity among family medicine residents. DESIGN: Descriptive study using an online survey. SETTING: Department of Family Medicine at the University of Ottawa in Ontario. PARTICIPANTS: A total of 54 first- and second-year residents. MAIN OUTCOME MEASURES: Family medicine residents’ involvement in research activities, perceived quality of their mandatory scholarly project, intentions for publication and presentation, and attitudes toward potential barriers to and facilitators of conducting high-quality research. RESULTS: Of the 54 residents, 20 (37%) reported that their project was of high quality, 6 (11%) intended to publish their findings, and 2 (4%) intended to present their findings. Respondents indicated that the main barriers to conducting high-quality research were lack of time, interest, and scholarly skills. The proposed solutions to increase participation in scholarly work were to allow full research days to be used in half-day increments and to offer a journal club where residents could learn scholarly activities. CONCLUSION: Family medicine residents found several factors to be considerable barriers to completing the required family medicine resident scholarly project. This indicates that there is a need to change the current approach to developing scholarly skills in family medicine. Greater allotment of and flexibility in protected research time and more sessions focused on developing scholarly skills might facilitate scholarly activity among family medicine residents.